Optimalisasi Tertib Arsip Dan Kualitas Layanan Kearsipan Pada Bidang Penyelenggaraan Haji Dan Umrah Kantor Wilayah Kementerian Agama Provinsi Sulawesi Barat - Sutrawati; Samad, Abdul; Rukaiyah, St (Jurnal Online Manajemen ELPEI, 2025)
This research aims to see efforts to realize the goals of archival management in the Hajj and Umrah Organizing Sector at the Regional Office of the Ministry of Religion, West Sulawesi Province. namely, Orderly Optimization of Archives and Quality of Archives Services through maximizing institutional awareness of the prospects for archives policies, quality of archives services, archives funding, archives management, archives organizations, archives infrastructure and facilities, and archives resources. The method used is a qualitative descriptive approach. Direct interviews from various informants, namely the Head of the Regional Office of the Ministry of Religion, West Sulawesi Province, the Head of the Hajj and Umrah Organizing Division, Archives Managers and Archives Service Users were carried out to collect data. Next, the data obtained will be analyzed and studied by researchers. The research results show that the optimization of orderly archives and the quality of archival services in the field of organizing the Hajj and Umrah has been carried out well in 3 aspects, namely orderly archive policy, archive management and human resources. However, there are 3 (three) that still need to be optimized, namely orderly facilities and archival infrastructure, orderly organization and archival funding.